Nurse burnout and quality of care: Cross-national investigation in six countries - Poghosyan, Lusine; Clarke, Sean P.; Finlayson, Mary; Aiken, Linda H. (Research in nursing & health, 2010)
We explored the relationship between nurse burnout and ratings of quality of care in 53,846 nurses from six countries. In this secondary analysis, we used data from the International Hospital Outcomes Study; data were collected from 1998 to 2005. The Maslach Burnout Inventory and a single‐item reflecting nurse‐rated quality of care were used in multiple logistic regression modeling to investigate the association between nurse burnout and nurse‐rated quality of care. Across countries, higher levels of burnout were associated with lower ratings of the quality of care independent of nurses' ratings of practice environments. These findings suggest that reducing nurse burnout may be an effective strategy for improving nurse‐rated quality of care in hospitals. © 2010 Wiley Periodicals, Inc. Res Nurs Health 33:288–298, 2010